Filmes comestíveis a base de combinações de celulose bacteriana e pectina com polpas de frutas - Viana, Rayra Melo (2017)
The industry mainly uses packaging materials derived from petroleum due to its favorable characteristics, such as good mechanical strength, but those materials are non-biodegradable, accumulating in the environment. Thus, the development of packagins materials derived from natural sources is well studied. The addition of fruit purees into films is a way of incorporating sensory attributes such as color and flavor, besides incorporating polysaccharides which may contribute for film formation as well as sugars which act as plasticizers. In this study, films were made with different proportions of nanofibrillated bacterial cellulose (NFBC) and pectin, added with two fruit purees (mango and guava), and sorbitol was used as plasticizer. A control group was also made without addition of any fruit purees. The films were characterized by visual aspect, tensile tests, water vapor permeability (WVP) and Fourier Transform Infrared spectroscopy (FTIR). Guava films presented higher water vapor permeability (WVP), tensile strength and elastic modulus than mango films, which presented better elongation at break. For both mango and guava films, 50-75% NFBC pectin provided the best tensile strength values. 25% NFBC was enough to lower the WVP of the guava-containing films, while, 75% NFBC were required to significantly lower the water vapor permeability of mango-containing films.